EXISTENTIAL AND NON-FACTIVE PRESUPPOSITION IN JANE AUSTEN’S NOVEL SENSE AND SENSIBILITY - Dian Anik Cahyani (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2016)
Presupposition in Sense & Sensibility is interesting subject because it is a linguistic phenomenon and a typical phenomenon. Presupposition can be analysis in many fields, one of them is a novel. Novel is one of literature field that interested to be learn because the language of the novel is long lives. The focuses in thisstudyare to describe the existential and non-factive presupposition in Sense & Sensibility novel.